Experimental and numerical study of nanofluid effects on heat transfer in unmanned aircraft cooling systems - Erdogan, Beytullah; Gunes, Abdulsamed; Bayramoglu, Kubilay (Elsevier, 2025)
This article investigates the use of nanofluids as an alternative to conventional coolants in radiator-based unmanned aerial vehicles (UAVs) cooling systems, aiming to enhance heat transfer performance, reduce energy consumption, and extend flight duration. Experimental and computational fluid dynamics (CFD) analyses were conducted under controlled conditions with a coolant inlet temperature of 70 degrees C, coolant flow rate of 22 L/min, and air velocities of 8, 10, and 12 m/s. Mono nanofluids (Al2O3, ZnO, CuO), binary hybrid nanofluids (CuO + ZnO), and ternary hybrid nanofluids (Al2O3+ZnO + CuO) at respective concentrations of 0.3 %, 0.15 %, and 0.1 % by volume were tested against pure water. Experimental results showed that the ternary hybrid nanofluid achieved the highest cooling load improvement, with up to 20.1 % enhancement compared to pure water. Among mono nanofluids, Al2O3 and CuO improved cooling loads by up to 17.9 % and 16.3 %, respectively. CFD simulations exhibited strong agreement with experimental results, showing a maximum deviation of 6.64 %, and confirmed that hybrid nanofluids offered the highest numerical heat transfer rate (10.93 kW). Additionally, it was observed that the use of nanofluids led to more significant temperature drops along the radiator, with a maximum fluid temperature change of 8.94 degrees C in the hybrid nanofluid.
Keywords: Nanofluid; Heat transfer enhancement; CFD; Panel radiator; Ternary